Efficiency of Public Procurement Function in Moroocco (American Journal of Economics and Business Innovation, 2024)
Public procurement, involving the public sector’s purchase of goods, services, or works from the pri-vate sector, accounts for 13-20% of global GDP (The World Bank, 2020). In Morocco, this sector rep-resents 17% of GDP (The World Bank, 2014) and is a crucial source of business for SMEs, which make up 95% of all businesses (Augier, Castel & El Malki, 2019). The efficiency of public procure-ment is a central issue in research due to its strategic, economic, and managerial impact (Kakwezi & Nyeko, 2019). While past research often focused on practical assessments (Flynn & Davis, 2014) and overlooked the market structure (KLEMPERER, 1999), based on a renewal of the game auction model for first price sealed bid auctions, along with both a qualitative and quantitative empirical research , this paper examines Moroccan public procurement efficiency from a market-based, game auction model perspective. It demonstrates that Morocco’s predominant open tender procedure exhibits pat-terns of an efficient game auction model with a Bayesian Nash equilibrium expression , suggesting opportunities for maintaining and improving the open tender meachnism itself and the surrounding procurement mechanisms.